Fun with English: Belajar Bahasa Inggris Lewat Permainan dan Aktivitas Seru untuk Siswa Sekolah Dasar di Kawasan Teluk Tomini - Husain, Nurlaila; Ali, Sri Widyarti (Yayasan Daarul Huda Kruengmane, 2024)
English language learning for students often faces challenges in the form of less attractive and monotonous teaching methods, leading to low interest and motivation to learn. The community service activity,